Predictors of Rape Myth Acceptance Among South Asian Students in Canada - Randeniya, Dayanga (Violence against women, 2025)
Transmission of rape myths is expected in every culture, yet limited research exists on rape myth acceptance (RMA) within global South Asian (SA) diasporas. We examined whether gender, attitudes toward gender roles, and patriarchal beliefs contributed to RMA among young SA adults in Canada. An ethnically diverse sample of 116 (ages 17–25) students, comprising equal numbers of men and women and domestic and international students, completed an online survey. SA students were generally egalitarian with low RMA similar to the majority of North American samples. As predicted, male gender, traditional attitudes towards SA women, and patriarchal beliefs were strong predictors of RMA.